Which Type of Atrophic Acne Scar (Ice‐pick, Boxcar, or Rolling) Responds to Nonablative Fractional Laser Therapy?. Issue 3 (21st January 2014) - Sardana, Kabir; Manjhi, Mukesh; Garg, Vijay K.; Sagar, Vivek
<x xml:space="preserve">Abstract</x> Background Few studies have examined the role of fractional lasers in individual acne scars (ice‐pick, box car, rolling) using objective assessment tools in darkly pigmented skin. Objective To evaluate the effect of 1, 540‐nm fractional lasers on individual acne scars. Methods and Materials A prospective interventional study was conducted in 35 patients using a 1, 540‐nm fractional laser. Six sessions were performed with four passes per session and a dose varying from 70 to 100 mJ to maximize the DWR. A self‐devised objective assessment tool with dose settings to optimize the depth‐to‐width ratio (DWR) and a visual analog scale (VAS) were used to count individual atrophic scars. Final results were assessed 6 months after final laser treatment. Results Acne scar reduction efficiency was used to validate the improvement of individual scars, a meaningful difference was considered as 51% or greater improvement. The boxcar scars (52.9%) responded better than the rolling (43.1%) and ice‐pick scars (25.9%), with statistically significant improvement (p < .05) seen in boxcar scars after four sessions. Overall VAS scores revealed significant improvement (p < .001). Conclusion Using an objective evaluation tool, an erbium‐doped glass laser was found to improve atrophic acne scars, markedly so for boxcar and rolling scars. The VAS score overestimated improvement because of its subjective nature.